IMPLEMENTASI STRATEGI PEMBELAJARAN KOOPERATIF LEARNING DALAM KURIKULUM 2013 MATA PELAJARAN PAI - Yulia Haliza Lubis; Syukur Manik; Neliwati (STAI Pelabuhan Ratu, 2023)
This study aims to find out how the implementation of the cooperative learning model (group study) and what are the supporting and inhibiting factors in the subject of Islamic Religious Education in Schools. The implementation of cooperative learning strategies needs to be continuously developed, because it is suspected to be able to improve student learning outcomes. On the other hand cooperative strategy learning is expected to develop learning outcomes in the form of tolerance, accepting diversity, and developing social skills. The teacher must be creative, this is the responsibility of the profession he carries out, the teacher must be able to use and develop cooperative methods in accordance with existing conditions. By using the cooperative method it is proven that communicative communication has occurred.